Análise dos principais elementos teórico-metodológicos utilizados por autores da geografia ao estudar o Sudoeste do Paraná - Abrão, Joice Aparecida Antonello (2012)
This research has like purpose to analyze a thesis and four dissertations of the human Geography in that the writers study the territory dynamics of the agriculture in the Southwest of the Paraná. We do parallel of the main concepts and conceptions utilized by writers chosen, after all to identify and to analyze as they interpret the familiar agriculture in the southwest of the Paraná. So, we organize, to each work, a board synthesis, with the intuition of the introduce conceptions of Geography, space, territory, development and familiar agriculture present in the thesis The process modernization of the agriculture in the Southwest of the Paraná of Roseli Alves dos Santos and in the dissertations Rural syndicalism and familiar agriculture in the municipality of Francisco Beltrão PR , The COAGRO and its process territorialization in the Southwest of the Paraná , The territory dynamics of the agribusineses handiwork of Francisco Beltrão/PR , and Territorialization of dairy and tobacco production in the district Itaíba Marmeleiro/PR respectivily, written by Lizandra Pirin, José Marcos Sinhorini, Marcio Freitas Eduardo and Luis Carlos Braga. In the orientation of geographic analysis, we observe notorious ancestry to the historical-critical conceptions, fastened to study of the Marxist theory. The territory is in the center of the interpretations in practicality all works; your comprehension passes by process historic and is had explain the conflict of classes, of groups, of social division and territorial of the work, the capital valorization process, of the productive force, of the relations of consumption etc. No, there are in the analyzed works conceit conformity about development and familiar agriculture in the Southwest of the Paraná, what us take, from the altogether analysis of the works, the dynamic interpretation of these concepts from of the combination of different elements territorials.